Quantifying CH4 emissions in hard coal mines from TROPOMI and IASI observations using the wind-assigned anomaly method - Q. Tu; Q. Tu; M. Schneider; F. Hase; F. Khosrawi; B. Ertl; B. Ertl; J. Necki; D. Dubravica; C. J. Diekmann; C. J. Diekmann; T. Blumenstock; et al. (Atmospheric Chemistry and Physics, 2022)
Intensive coal mining activities in the Upper Silesian Coal Basin (USCB) in southern Poland are resulting in large amounts of methane (CH4) emissions. Annual CH4 emissions reached 448 kt according to the European Pollutant Release and Transfer Register (E-PRTR, 2017). As a CH4 emission hotspot in Europe, it is of importance to investigate its emission sources and make accurate emission estimates.